Tell Bleibil, Jordanien. Die Arbeiten des Jahres 2019 - Ahrens, Alexander (e-Forschungsberichte des DAI, 2020)
As part of the “Wadi Shuʿaib Archaeological Survey Project (WSAS)”, excavations are carried out at the site of Tell Bleibil (Tall Bulaybil), located at the mouth of the alluvial fan of the Wadi Shuʿaib in the southern Jordan Valley, since 2017. The excavations conducted in 2019 continued to excavate the Iron Age settlement´s city wall, preserved to a height of almost four meters. Additionally, a corner of a bastion or tower protruding from the fortification wall was revealed. The exterior side was coated with a layer of yellow chaff tempered plaster which partially was still preserved in situ.